Contribution to the epidemiology of cervical cancer in Peru - Valdivia Ponce, Eduardo (2015)
The AA present a study on the epidemiology of cervical cancer, based on a review of medical records of 5,092 patients with this cancer in 10 years and attended the National Institute of Neoplastic Diseases, a hospital with 120 beds, specialized and State, which referred patients arrive throughout the Republic. This study suggests a link between sexual relations and the development of cervical cancer, similar to some VD form (as in the acuminatus genital warts (?)). In addition, it is noted that aggravate this link, other factors, including socio-economic and cultural poverty.